Assertive behavior in a man's life and the risk of developing an oncological disease - Kinas-Budzisz, Joanna; Ramlau, Rodryg (Contemporary Oncology/Współczesna Onkologia, 2002)
This work presents the concept of assertion in the etiology of cancer and the process of coping with it with regard to scientific research confirming the relationship of an oncological disease with a patient's personality. It is based on the definition formulated by Association for Advancement of Behavior Therapy which states that assertion is a set of interpersonal types of behavior expressing feelings, attitudes, opinions or rights of a given person in a direct, decisive and honest way respecting the feelings, attitudes and rights of other persons. Assertion may comprise expression of all kinds of feelings, e.g. anger, joy, indignation, but they are expressed in a way which does not violate other people's rights. In contrast, aggressive behavior while expressing feelings and attitudes does not accept the same elements in others. Three types of non-assertive behavior are distinguished. The passive type relates to the Type-C behavior, which in view of psychology predisposes to an oncological disease. Assertion correlates with the perceived self-efficacy social support, internal control and optimism. The group of 130 patients was distributed two kinds of anonymous questionnaires and assertive skills tests. After completing them the patients could comment on them during an individual meeting with a psychologist. Four groups of patients were distinguished: I group - 27 persons - assertion present; II group - 103 persons - no assertion; III group - 23 persons - non-assertive aggressive behavior; IV group - 80 persons - non-assertive submissive, passive behavior. It is clear that patients have insufficient knowledge about assertion. Most frequently displayed type of behavior in life - submissive or aggressive. The group of assertive persons was dominated by women. The group of non-assertive behavior dominated by a passive style (mainly men). The lack of assertive skills may lead to a psychosomatic illness. Teaching assertive behavior is one of the methods o f preventing illness.